Gangguan Berbahasa pada Anak Usia 10 Tahun - Patrisia Deni Sidebang; Oky Ferdian Gafari; Anggi Puteri; Abdurrahman Adisaputera (Prodi Sastra Inggris UKI, 2023)
Based on Reza's medical history and development, there are indications that the language disorder he experienced is related to the presence of a medical history at birth, namely tongue-tie or ankyloglossia. Where when Reza was just born there was a kind of binding or barrier on the tongue so that the range of motion of the tongue was not free. Based on observations from his medical history, Reza experienced tongue-tie where he became difficult to stick out his tongue and became one of the causes of being slurred. In addition, tongue-tie also affects the way Reza eats, speaks, and swallows. In this study, qualitative methods were used by applying interview techniques to Reza's parents and also making observations when Reza communicated with his environment. The main goal is to obtain in-depth data on the language disorders experienced by the ten-year-old child. The limited pronunciation of R experienced by Reza makes it difficult for him to pronounce some words related to the letter R. This then makes the words and sentences spoken by Reza sound strange and incorrect. So he becomes difficult to communicate with his peers. To overcome these limitations, Reza took the initiative to write them on paper or on the ground when playing together.this limitation also did not become an obstacle for Reza to make friends and adjust, because some of his playmates had often communicated with him so that conversations between them seemed to run smoothly and well even though sometimes there were still moments between them that were difficult to understand the meaning of Reza's sentence. Limitations in language learning are things that need to be considered, so a special approach is needed in providing language training that is in accordance with Reza's conditions. With regular learning carried out every day with the surrounding environment, it is hoped that Reza will experience an improvement in his communication skills and also expected environmental awareness of Reza's condition.